The Influence of Monetary Indicators on the Inflation Rate in Indonesia for the 2020-2024 Period Using the Vector Error Correction Model Approach - Shafa Salsabila Dewi; Gita Asri Rani; Rhevaira Kayla Zhafirah (Jurnal Ekonomi Pembangunan, 2025)
This study examines the influence of monetary indicators on inflation in Indonesia during 2020–2024 using the Vector Error Correction Model. The variables analyzed include the BI Rate, money supply, and the exchange rate. Monthly time series data were obtained from Statistics Indonesia and the One Data Trade Portal of the Ministry of Trade to strengthen the empirical foundation. The results show that in the short run, only the exchange rate significantly affects inflation, while the BI Rate and money supply show no significant impact. In the long run, money supply and the exchange rate were found to influence inflation significantly, whereas the BI Rate remained insignificant. These findings suggest that real monetary conditions and external stability drive Indonesia's inflation dynamics more than interest rate policy. Therefore, maintaining exchange rate stability and managing liquidity are crucial for sustaining price stability and improving the overall effectiveness of monetary policy in the long term.